Diagnosis and Therapy of Olfactory Dysfunction - State of the ArtThe neglected sense-new evidence highlights the significance of the human sense of smell - Mueller, Christian A.; Renner, Bertold (Wiener Medizinische Wochenschrift, 2021)
Recent research shows that the human sense of smell seems to be more efficient than previously believed and to have a major impact on our health condition and quality of life. During the COVID-19 pandemic, an increased clinical interest has become evident for the SARS-CoV-2 related impact on olfactory function. This article highlights important aspects in the diagnosis and therapy of the chemical senses.
CRIS-Team WoS Importer:2021-12-10